UPAYA GURU DALAM MENGATASI TOXIC PARENT BAGI SISWA BROKEN HOME KELAS TINGGI - Dewi Ummu Kalsum (MEDIA DAN STRATEGI PEMBELAJARAN, 2025)
Based on observations, it was found that students from broken homes tend to show disrupted social behavior due to unsupportive parenting patterns. This study aims to describe the dominant behavior that appears in broken home students and teachers' efforts to overcome toxic parents in high classes. This type of research is qualitative research using a descriptive approach method. The data collection techniques used are observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman model. The study results showed that the dominant behavior of broken students from home students disobedience, aggression, isolation, and excessive control. To overcome this, teachers apply an individual approach, provide motivation and guidance, establish communication with families, create a safe school environment, and carry out collaborative projects. This study emphasizes the importance of teachers as facilitators to support the development of students from broken homes.